Comparison of reproductive investment in native and non‐native populations of common wall lizards reveals sex differences in adaptive potential. Issue 11 (17th May 2017) - MacGregor, Hannah E. A.; While, Geoffrey M.; Uller, Tobias
Abstract : Non‐native animals can encounter very different environments than those they are adapted to. Functional changes in morphology, physiology and life‐history following introduction show that organisms can adapt both fast and efficiently. It remains unclear, however, if female reproductive characters and male sexually selected behaviour show the same adaptive potential. Furthermore, the invasion success and evolutionary trajectory of non‐native species might often depend on the ability of the sexes to coordinate shifts in characters associated with reproductive strategy. The common wall lizard, Podarcis muralis, has been repeatedly introduced from southern Europe to England over the past 80 years. Lizards in England experience a cool, seasonal climate that effectively restricts recruitment to the first clutch of the season, whereas in their native range up to three clutches per season recruit. As a consequence, both females and males in non‐native populations should benefit from reducing or even eliminating their reproductive investment in second clutches. Using a combination of field data and experiments, we show that non‐native females produce relatively larger and heavier first seasonal clutches and smaller and lighter second seasonal clutches compared to native females. In contrast, non‐native and native males do not differ in their territorial and sexual behaviour later in the season. An adaptive shift in male seasonal reproductive investment may be constrained because males use breeding females as cues for sexual behaviour. If this is so, we expect a general pattern across climatic regimes whereby female reproductive investment evolves first, with responses in males lagging behind.